Determinants of the regional demand for higher education in the Netherlands : a gravity model aproach - Sá, Carla Angélica da Silva Pinto de (2004)
Studies on the determinants of the demand for higher education typically emphasize the relevance of socio-economic factors, but leave the spatial dimensions of the prospective students' university choices largely unexplored. In this study, we investigate the determinants of university entrance for Dutch high school graduates in 2000, and pay particular attention to the attractiveness of the university, both in terms of its accessibility and the educational quality of its programme. We combine cross-section data on the region of origin of the high school graduate and the university destination region for first-year students with regional and university characteristics in a production- constrained gravity model. The main finding of the study is that the behaviour of prospective students is governed by a distance deterrence effect and a downward rent effect, but a positive impact results from regional/urban amenities rather than from the educational quality of the university programmes.